Healthcare-Associated Infective Endocarditis: a Case Series in a Referral Hospital from 2006 to 2011 - Francischetto,Oslan (2014)
Background: Healthcare-associated infective endocarditis (HCA-IE), a severe complication of medical care, shows a growing incidence in literature. Objective: To evaluate epidemiology, etiology, risk factors for acquisition, complications, surgical treatment, and outcome of HCA-IE. Methods: Observational prospective case series study (2006-2011) in a public hospital in Rio de Janeiro. Results: Fifty-three patients with HCA-IE from a total of 151 cases of infective endocarditis (IE) were included. There were 26 (49%) males (mean age of 47 ± 18.7 years), 27 (51%) females (mean age of 42 ± 20.1 years). IE was acute in 37 (70%) cases and subacute in 16 (30%) cases. The mitral valve was affected in 19 (36%) patients and the aortic valve in 12 (36%); prosthetic valves were affected in 23 (43%) patients and native valves in 30 (57%). Deep intravenous access was used in 43 (81%) cases. Negative blood cultures were observed in 11 (21%) patients, Enterococcus faecalis in 10 (19%), Staphylococcus aureus in 9 (17%), and Candida sp. in 7 (13%). Fever was present in 49 (92%) patients, splenomegaly in 12 (23%), new regurgitation murmur in 31 (58%), and elevated C-reactive protein in 44/53 (83%). Echocardiograms showed major criteria in 46 (87%) patients, and 34 (64%) patients were submitted to cardiac surgery. Overall mortality was 17/53 (32%). Conclusion: In Brazil HCA-IE affected young subjects. Patients with prosthetic and native valves were affected in a similar proportion, and non-cardiac surgery was an infrequent predisposing factor, whereas intravenous access was a common one. S. aureus was significantly frequent in native valve HCA-IE, and overall mortality was high.